Associação de óleos essenciais e vírus entomopatogênico no manejo de Spodoptera frugiperda (Lepidoptera: Noctuidae) - Zorzal,Alexandra Aparecida (2018)
The fall armyworm Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae), considered the main pest of maize in Brazil. It is a polyphagous insect, with great capacity to infest different cultures of economic importance. Their management is usu